Intelligent systems in science and information 2014 extended and selected results from the Science and Information Conference 2014 - Arai, Kohei; Kapoor, Supriya; Bhatia, Rahul (Springer International Publishing, 2015)
The book Intelligent Systems in Science and Information 2014 is the carefully edited collection of 25 extended chapters from selected papers in the field of Computational Intelligence that , which received highly recommended feedback during the Science and Information Conference (SAI) 2014 review process. All chapters have gone through substantial extension and consolidation and were subject to another round of rigorous review and additional modification and represent the state of the art of the cutting-edge research and technologies in the related areas.